Adaptation and pre-test of a shortened Stepping Stones and Creating Futures intervention focused on HIV for young men in rural South Africa - Andrew Gibbs; Dumsani Gumede; Oluwafemi Adeagbo; Yandisa Sikweyiya; Esnat Chirwa; Smanga Mkhwanazi; Manono Luthuli; Zakhele Xulu; Carina Herbst; Thembelihle Zuma; Siphesihle Hlongwane; Nonhlanhla Okesola; et al. (Public Library of Science (PLoS), 2023)
Men's engagement in HIV prevention and treatment is suboptimal, including in South Africa. We sought to address this through adapting an evidence-based intervention, Stepping Stones and Creating Futures (SSCF), to strengthen its HIV content and provide a more scalable (shorter) intervention in rural South Africa. We then conducted a mixed methods pre-test of the intervention among young men aged 18-35 years. To adapt SSCF, we reviewed the current evidence base and worked with male Peer Navigators to update the SSCF theory of change (ToC) and manual. The revised intervention was ~45 hours (9 sessions) as opposed to ~63 hours and included a greater focus on HIV prevention and treatment technologies. Overall, 64% (n = 60) of men approached agreed to participate in the intervention, uptake (attending one session) among those who agreed was n = 35(58%) and retention (attending 6 or more sessions) was n = 25(71%). Qualitative data emphasized the intervention was acceptable, with young men describing it as something they liked. The qualitative data also broadly supported the intervention ToC, including the normalization of HIV in men's lives, and the importance of health for men in achieving their life goals. However, it also highlighted the need to focus more on HIV-related stigma and fear, and the importance of HIV self-testing kits in encouraging testing. We revised the ToC and manual in light of this data. The adapted SSCF is acceptable and supports the ToC. Next steps is an evaluation to look at effectiveness of the intervention.